(untitled) (Orfeu, 2023)
In July 2015, the Statute for People with Disabilities, Law No. 13,146, was launched in Brazil, which makes it clear that people with disabilities also have the right to learning in all educational areas (BRASIL, 2015). With that in mind, Music Degree Courses also need to adapt to this scenery of demand and train future teachers to meet the diversity of students, consciously and efficiently. Therefore, tracing the disciplines overview and conducting discussions based on the analysis of the curricula, programs, menus and pedagogical projects of the courses, this research aimed to investigate the program proposal of Music Licentiate courses of the Brazilian Federal Universities regarding Musical / Inclusive Education aspects, in order to train music teachers to support the inclusion of students with disabilities and disorders. As a result, it was observed that only 17 of the 35 Federal Universities offer such content, highlighting the need to expand and deepen the disciplines related to Music and Inclusion in the reality of Brazilian Federal Universities. Thereby, having presented an overview of the disciplines and encouraging discussions about the results and data collected, this work may encourage further in-depth research on the theme of musical teacher education and inclusion, in order to contribute to the improvement of discussions and the expansion of such disciplines offering in all Federal Universities. Keywords: Musical Education. Special Education. Inclusion. Teacher’s Formation.